PENGARUH BAURAN RITEL TERHADAP LOYALITAS KONSUMEN DI SUPERMARKET SRI RATU PETERONGAN - Wijayanto, Bebet; Prihartini, Apriatni Endang; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2013)
This research aims to investigate customer’s perception concerning retailing mix that has been done by Sri Ratu Peterongan Supermarket, its influence towards customer loyalty, and which variable influence customer loyalty the most. Population that was used is Sri Ratu Peterongan Supermarket’s customer who has SATU card. Number of sample is 100 people. Sampling technique that was used is nonprobability sampling. Sample was taken by purposive sampling method. Data which is obtained was analyzed qualitatively and quantitatively using validity and reliability test, crosstab analysis, correlation coefficient, simple linear regression, double linear regression, determination coefficient, t and F test with SPSS 18 for windows. Research results are retailing mix, consist of store location, merchandise, price, customer service, promotion, and store atmosfer, have positive influence towards customer loyalty, and customer service variabel has the biggest influence towards customer loyalty.